2020
DOI: 10.1101/2020.08.31.276360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying Isl1 genetic lineage in the developing olfactory system and in GnRH-1 neurons

Abstract: During embryonic development, symmetric ectodermal thickenings (olfactory placodes) give rise to several cell types that comprise the olfactory system, such as those that form the terminal nerve ganglion (TN), gonadotropin releasing hormone-1 (GnRH-1) neurons and other migratory neurons in rodents. Even though the genetic heterogeneity among these cell types are documented, unidentified cell populations arising from the olfactory placode remain. One candidate to identify placodal derived neurons in the develop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…We used conditional recombination of a reporter to identify temporally distinct, lineally-related subsets of Ascl1+ OE precursors (Cau et al, 2002; Cau et al, 1997; Guillemot et al, 1993; Murray et al, 2003; Tucker et al, 2010) shortly after the initial OE morphogenesis. Similar approaches have been used to assess temporally discrete populations of Ascl1+ precursors in the spinal cord, cerebellum, and cerebral cortex (Allaway et al, 2020; Battiste et al, 2007; Sudarov et al, 2011; Vue et al, 2014) as well as for Isl1+ OE precursor fates (Taroc et al, 2020). The central role suggested for Ascl1 and other neurogenic genes in olfactory pathway development (Cau et al, 2002; Guillemot et al, 1993; Murray et al, 2003) led us to these experiments focused on Ascl1+ OE cells at the earliest stages of olfactory pathway differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We used conditional recombination of a reporter to identify temporally distinct, lineally-related subsets of Ascl1+ OE precursors (Cau et al, 2002; Cau et al, 1997; Guillemot et al, 1993; Murray et al, 2003; Tucker et al, 2010) shortly after the initial OE morphogenesis. Similar approaches have been used to assess temporally discrete populations of Ascl1+ precursors in the spinal cord, cerebellum, and cerebral cortex (Allaway et al, 2020; Battiste et al, 2007; Sudarov et al, 2011; Vue et al, 2014) as well as for Isl1+ OE precursor fates (Taroc et al, 2020). The central role suggested for Ascl1 and other neurogenic genes in olfactory pathway development (Cau et al, 2002; Guillemot et al, 1993; Murray et al, 2003) led us to these experiments focused on Ascl1+ OE cells at the earliest stages of olfactory pathway differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…We performed GFP/Meis2/HUCD triple immunofluorescence to distinguish among sustentacular cells and, apical and basal VSNs in the NICD inducible pups. As HUCD is only expressed in neuronal population [41], we considered Meis2+/HUCD-as non-neuronal sustentacular cells, Meis2+/HUCD+ as apical VSNs and Meis2-/HUCD+ as basal VSNs. The analysis in the inducible mice showed that 66.6% of the NICD: EGFP population became sustentacular and only 32.3% of the recombined cells were found to be VSNs (Fig.…”
Section: Conditional Lineage Tracing Confirms the Formation Of Notch1+ And Dll4+ Cells Frommentioning
confidence: 99%